The Medication adherence in elderly people referring to the primary health care centers and its effective factors in East Azerbaijan province -Iran: A mixed-method study - Dewi, Nurdiana (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
IntroductionThe high rate of population aging and the increasing use of multiple therapies has made Medication Adherence (MA) among the elderly very important issue. The aim of this study was to determine the level of MA and related factors in elderly people (60 years and over) with chronic disease referring to the Primary Health Care (PHC) centers in East Azerbaijan Province-Iran.Methods:This is a mixed-method study conducted in East Azerbaijan in 2020. The quantitative data were collected from 320 elderly people (60 years old and over). The qualitative data were collected from medicine experts, PHC providers and the elderly people. The data were collected using Medication Adherence Scale (MMAS-8) questionnaire, socio- demographic questionnaire and an open-ended questionnaire. The quantitative data analyzes was carried out using descriptive statistics and Chi-square, T-test, One Way ANOVA test, and the qualitative data analyzes was carried out using Content-Analysis method.Results:The mean score of MA was 3.14± 1.63. The majority of the elderly people, 251 (83.1%) had poor MA score. The most important factors affecting MA were categorized into four domains: the elderly self-esteem, provider-related factors, family-related factors, and other factors. The most important strategies for enhancing MA were divided into four domains: the education, medication management interventions, supportive measures and other strategies. The most important roles of the health system and the PHC providers were divided into six domains: the education, follow-up on medicine use, appropriate communication with the elderly, quality care provision, appropriate medicines preparation and administration, and collaboration with the elderly. The most important factors of non-adherence among the elderly were categorized in three domains: medicine related factors, elderly related factors and factors related to the access problems.ConclusionOur findings show that the mean score of the MA in the elderly referring to the PHC centers in East Azerbaijan province was low.